Sosialisasi Sport Massage pada Atlet Sepak Takraw kota Palu - Ningsih, Yuni Fitriyah; Agusman, Muhammad; Kandupi, Ardiansyah D.; Sianto, Moh. Ifkhal (Universitas Negeri Surabaya, 2023)
This study discusses the process of socializing sports massage implemented among sepak takraw athletes in Palu City. The aim of this research is to analyze the effectiveness and impact of sports massage socialization on the physical well-being and athletic performance. The research methodology involves a qualitative approach with data collection through in-depth interviews and direct observation of athletes and coaches involved in the socialization program. The research findings indicate that sports massage socialization has provided significant benefits in terms of muscle relaxation, injury recovery, and athletic performance enhancement. Regular training and understanding of massage techniques also contribute to effective implementation. However, some challenges such as limited resources and uneven understanding among athletes and coaching staff need to be addressed to improve the effectiveness of this socialization. This study underscores the importance of a holistic approach to athletes' physical preparation through the sports massage method and emphasizes the need for sustained support from various relevant parties.